Transformations of Medical and Vaccine Diplomacies in the COVID-19 Era - I. I. Arsentyeva (Vestnik MGIMO-Universiteta)
The pandemic has produced the global COVID-19 vaccine market with various stakeholders acting in their economic self-interest. At the same time, some governments use vaccines for pursuing national interests and expanding their international influence. Using scientific works on the topic and documents from WHO, GAVI, WTO, IMF, government documents and think tank reports, the author analyzes vaccine diplomacy as a branch of medical diplomacy and identifies changes that occur under pandemic impact. The article examines the current policy of China, as it has achieved the most notable success in medical services export, primarily to developing countries, and Chinese pharmaceutical companies play a prominent role in the global vaccine market. It raises serious concerns of the West, which accuses Beijing of using coronacrisis to establish a new (China-centric) world order. It is concluded that government capacity to protect public health and control epidemic spread is among the significant criteria for evaluating the effectiveness of State policy, and its own vaccine industry begins to be regarded as an important element of national security. There is also a considerable increase in the role of healthcare in foreign policy of a number of States using medical and vaccine diplomacies as a means of achieving political goals. COVID-19 vaccines are becoming a strategic asset that affects the country’s position on the world stage and generates a new field of geopolitical rivalry. But at the same time, vaccine diplomacy could serve as a dialogue platform in cases when interstate relations are in a deep crisis. And it may lead to awareness of the need to train specialists in the field of medical diplomacy.